General calculation method of power boundary of multiport power electronic transformer - Li, Junchi; Wu, Junyong; Xiong, Fei (Frontiers in Energy Research, 2024)
In the multiport power electronic transformer (MPET), cascaded H-bridge (CHB) converters form the medium voltage AC port, while multiple low voltage DC ports are constructed by paralleling dual active bridge (DAB) converters into clusters. Uneven power distribution among these ports leads to power imbalances, risking over modulation in CHB converters with high power generation or load power. This study proposes a general calculation method (GCM) for determining the power boundary of MPETs, enabling the adjustment of reference power for each DC port to prevent over modulation. The GCM is designed to handle scenarios with multiple simultaneous power flow directions. The effectiveness of the GCM is verified by DC port power boundary simulation results of two independent DC bus structure multiport power electronic transformers. The proposed method provides a straightforward approach to calculating power boundary for MPETs with multiple power flow directions, ensuring efficient power management.